Remarks on criticality and crisis in pure exchange economies - Pejsachowicz, Jacobo (Topological Methods in Nonlinear Analysis, 2022)
In the framework of the theory of Equilibrium Manifold of a Pure Exchange Economy, introduced by Balasko, we give a rigorous definition of a crisis transition and establish some infinitesimal criteria which distinguish unavoidable crises from other critical equilibria. Our approach builds on the relationship between the mathematical notions of branching, envelopes, and the intrinsic derivative.